Effect of Polymer Concentration on Salt Rejection of Polysulfone Membrane - Ismail, Azman; Mohd Tajuddin, Ramlah (International Journal of Engineering and Technology, 2019)
A newly fabricated microfiltration membrane was used to evaluate the effect of polysulfone concentration on salt rejection for seawater. The material chosen in this study was polysulfone (PSF). The dope formulation was gathered from past researches via literature review. The gathered formulation were 10:89:1, 15:84:1, 20:79:1 and 25:74:1 based on weight to weight percentage (wt%) for PSF:NMP:PVP composition. The formulations were named as PSF1, PSF2, PSF3 and PSF4. The membranes were fabricated by using dry wet phase inversion method with pneumatically control flat sheet systems. The membranes were analyzed using Scanning Electron Microscope (SEM) to understand the morphology and surface pore size. 25 liters of seawater was collected from Port Dickson beach in Malaysia to evaluate water flux and salt rejection for each membrane sample. SEM images result shows that membrane pore size decreases by PSF1 > PSF2 > PSF4 > PSF3. PSF1 have the highest pore size ranging from 1.83 Î¼m to 2.57 Î¼m. Meanwhile, PSF3 have the lowest pore size among all samples used, which is 273 nm â€“ 542 nm. Cross sectional structure shows fingerlike structure and skin layers developing on the membrane. Water flux test shows a decrement from PSF1 > PSF2 > PSF3 > PSF4. The highest water flux was recorded at 12.5 l/m2.hr, and the lowest was at 1.1 l/m2.hr. For salt rejection, PSF4 recorded the highest rejection of 62% while PSF1 recorded the lowest rejection, which is 10.5%. This shows that the increment of polysulfone concentration in membrane solution would decrease water flux while increasing water rejection at the same time. The best membrane formulation in this research is PSF2 with PSF:NMP:PVP at 15:84:1.Â